STATISTICAL DATA PROCESSING TRAINING THROUGH STATISTICAL PRODUCT AND SERVICE SOLUTION (SPSS) SOFTWARE APPLICATION AT PRINCE DIPONEGORO ISLAMIC RELIGIOUS INSTITUTE NGANJUK: PELATIHAN PENGOLAHAN DATA STATISTIKA MELALUI APLIKASI SOFTWARE STATISTICAL PRODUCT AND SERVICE SOLUTION (SPSS) DI INSTITUT AGAMA ISLAM PANGERAN DIPONEGORO NGANJUK - Nik Haryanti; Muhamad Ali Anwar; Yunis Hidayati; Alfin Yuli Dianto (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2022)
Statistics can be used to state a collection of facts, generally in the form of numbers arranged in tables or diagrams that describe or describe a problem. Applying statistics to research is an advantage that a researcher has when conducting research. In addition to making it easier for students to analyze data, students also have a relatively shorter time in calculating the data they get.  Statistical data processing training using SPSS for students is carried out with face-to-face methods, and spss program application practices run smoothly and well. Activities are carried out gradually from the presentation of concepts that are continued by the practice of the given concepts. Participants follow the activity enthusiastically; this is indicated by questions and responses regarding the material provided. Statistical program training for students in this community service program that has been carried out is expected to provide the understanding and teachers' ability to use statistical programs that will have an impact on increasing research productivity at IAI Pangeran Diponegoro Nganjuk